Al-Islām fī Indūnīsīyā: Itārujadīd - Arief Subhan (Studia Islamika, 2006)
Intellectual Muslims generally began to attain prominence in the early 20th century, in line with the growing modernization of the Islamic world. During this period, the Islamic world faced colonialism and imperialism which had unthought-of of implications for the wider Muslim community. The struggle against colonialism sparked debate about jihad with a more varied and complex meaning. The cultural struggle that took place between Islam and the West gave rise to a "cultural exchange" that not only resulted in the rise of the social class that we now refer to as intellectual Muslims, but also created a new-found sense of enthusiasm and passion for debating lslamic doctrine and issues in the context of modern values.DOI: 10.15408/sdi.v13i2.569